Analisis terhadap Artificial Intelligence sebagai Subjek Hukum Pidana - Kurniawan, Itok (Mutiara: Jurnal Ilmiah Multidisiplin Indonesia, 2023)
This article discusses issues related to the existence of artificial intelligence as a legal subject, and criminal liability when artificial intelligence commits criminal acts. The purpose of this study is to find out the categorization of artificial intelligence as a legal object or legal subject, and to find out to whom criminal responsibility is assigned when artificial intelligence commits a crime. The research method used in writing this article is normative legal research, with a conceptual approach. The results of this study are that artificial intelligence is not a legal subject, because the actions carried out by artificial intelligence are only orders from its users, and for criminal acts committed by artificial intelligence, those who must be responsible are the creators of artificial intelligence or users of artificial intelligence